PENERAPAN METODE PENEMUAN TERBIMBING PADA MATERI HUBUNGAN ANTAR GARIS DAN SUDUT - Firmansyah, Firmansyah; Jaeng, Maxinus; Murdiana, I Nyoman (Aksioma, 2020)
Abstrak: The purpose of this study is to describe the application of guided discovery method that can improve student learning outcomes VII A grade SMPN 18 Palu on the material connection between lines and angles. The type of research used is classroom action research (CAR). The research design refers to the research design of Kemmis and Mc. Taggart consists of four components: 1) planning, 2) action, 3) observation and 4) reflection. The type of data used is qualitative data and quantitative data with data collection techniques are observation, interviews, field notes and tests. This research was conducted in two cycles. The results showed that the application of guided discovery learning methods can improve student learning outcomes by following the steps of guided discovery methods are: 1) the formulation of the problem, the researcher explains the subject matter regarding the relationship between lines and angles, the researcher distributes student activity sheet which contains questions concerning the material relations between lines and angles that must be completed by students. 2) data processing and constructing conjectures, students process data in the student activity sheet and arrange conjectures. 3) Examining the conjecture, the researcher examines the conjectures that have been prepared by students and provides guidance as needed if there is an error in compiling the conjecture. 4) verbalizing the conjecture, student representatives from each group present the results of the conjecture obtained and the researcher guides students to make correct conclusions about the material relations between lines and angles. 5) feedback, giving practice questions about the material of relationships between lines and angles to students. The results of this study indicate that classical learning completeness students in the cycle I is 50% and increased in the cycle II is 77%.